Evaluation indicators of the marketing strategies efficiency of value-based enterprises - Koval, Z. O. (Publishing House of Lviv Polytechnic National University, 2016)
The article presents indicators used for evaluating the enterprise marketing strategy efficiency with current approaches. Trends in evaluating marketing strategy of value-based enterprises are analyzed and specified. There are selected and grounded evaluation indicators of marketing strategies efficiency of value-based enterprises. The system of indicators corresponding to the selected principles and demands of value-based management as well as to the suggested efficiency evaluationcriteria is developed. The aim of this research is to analyze advantages and disadvantages of current evaluation indicators of marketing strategies efficiency in the process of their application as well as develop new indicators to meet the requirements of value-based enterprises. As a result of the research a system of indicators to carry out an objective and overall evaluation of the marketing strategy according to the integral efficiency indicator and in compliance with the requirements of value-based enterprise management is proposed. The research results can be applied in the evaluation model of the marketing strategy options at the value-based enterprises with the aim of choosing the best option.
Keywords: indicators of efficiency evaluation; marketing strategy; marketing strategy efficiency; strategy options; system of indicators; value-based enterprise